Radiosynthesis and preliminary in vivo evaluation of 18F-labelled glycosylated duramycin peptides for imaging of phosphatidylethanolamine during apoptosis. Issue 11 (25th September 2019) - Haskali, Mohammad B.; Denoyer, Delphine; Roselt, Peter D.; Hicks, Rodney J.; Hutton, Craig A.
Abstract : [ 18 F]-Labelled duramycin derivatives incorporating hydrophilic aminogalacturonic acid moieties were prepared as tracers for in vivo imaging of phosphatidylethanolamine during apoptosis. Abstract : Duramycin derivatives incorporating an [ 18 F]-labelled prosthetic group and one or two hydrophilic sugar amino acid moieties have been prepared as potential tracers for imaging of phosphatidylethanolamine during apoptosis. [ 18 F]FP-digalacto-duramycin exhibited a low Log  D, high renal clearance and low background activity and is a promising radiotracer for tracking apoptosis in vivo .